Colorectal carcinogenesis in germ-free and conventionally reared rats: different intestinal environments affect the systemic immunity - Vannucci, Luca; Stepankova, Renata; Kozakova, Hana; Fiserova, Anna; Rossmann, Pavel; Tlaskalova-Hogenova, Helena (International journal of oncology, 2008)
Intestinal microbiota are considered to play an important role both in colorectal tumor development and in the modulation of mucosal immunity. Studies on animals reared in germ-free (GF, without intestinal microbiota) versus conventional (CV, with regular microbiota colonization of the bowel) conditions can aid in clarifying the influence of bacteria on carcinogenesis and the anticancer immune response. The capability of the intestinal environment to modulate anticancer immunity not only at the mucosal but also at the systemic level is still an open question. In our study we found that, following the same protocol of colorectal cancer induction, GF rats developed less and smaller tumors than CV rats. The GF rats that did not develop cancer also presented a better anticancer immune response with an increase in NK, NKT, CTL, B cells and cytotoxicity in peripheral blood. We hypothesize that the lower antigenic challenge and the absence of the 'physiological inflammation', caused by the commensal microbiota in the gut of CV rats, may enhance the capability of the GF rats to develop more efficacious anticancer immune responses. The different levels of tolerance/regulatory mechanisms in GF versus the CV animals may modulate the anticancer response not only at the mucosal but also at the systemic immunity level.
Keywords: gnotobiologické modely; přirozená imunita; střeva; Animals, Newborn; Cell Line; Male; kolorektální nádory; Rats, Inbred Strains; Rats, Wistar; progrese nemoci; Cell Proliferation; Germ-Free Life; mužské pohlaví; inbrední kmeny potkanů; Disease Progression; potkani Wistar; lymfocyty; novorozená zvířata; Immunity, Innate; cytotoxické testy imunologické; krysa rodu Rattus; Cytotoxicity Tests, Immunologic; Animals; Carcinoma; ženské pohlaví; Lymphocytes; zvířata; buňky NK; Rats; karcinom; buněčné linie; proliferace buněk; Colorectal Neoplasms; Intestines; Female; Killer Cells, Natural